REPRESENTATION AND CAPABILITIES OF NON-MUSLIM CHINESE WOMEN AS REGIONAL HEADS IN SINGKAWANG CITY: A Siyasah Dusturiyyah Analysis - Ali Akhbar Abaib Mas Rabbani Lubis; Abdur Rozaki; Khoiruddin Khoiruddin (AL-TAHRIR, 2023)
The phenomenon of non-Muslim Chinese women being elected as regional leaders in Indonesia is considered unusual, especially when elected amid a predominantly Muslim population and the strengthening of Islamist movements in national politics. This article, therefore, analyses the representation and capabilities of non-Muslim Chinese women as regional heads in Singkawang City, Indonesia, from 2017 to 2022. In the Indonesian context, we refer to this case as a “triple minority.” The research used a socio-legal approach involving data condensation, data display, and conclusion/verification stages. The findings of this study indicate that the representation and capabilities of non-Muslim Chinese women as regional heads in Singkawang City from 2017 to 2022 align with the principles of constitutional politics (siyasah dusturiyah) and Indonesian laws. Non-Muslim Chinese women elected as regional heads of Singkawang City, despite being in a Muslim-majority environment, have succeeded in making Singkawang City the top-ranked Tolerant City in Indonesia.